Implementation of Digital Marketing in Building Brand Recognition Using Creative Content Formats and Paid Advertising on Instagram and Tiktok Social Media Platforms for Michil Msme - Astri Nur Rahmawati; Adinda Rizki Luthfiyyah; Fitri Dewi Afiany (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Michil is a Micro, Small, and Medium Enterprise (MSME) based in Bandung City that operates in the Food and Beverage sector, focusing on chili oil-based menu products. As a newly growing MSME, Michil needs to expand its effective strategies to enhance brand visibility in the eyes of consumers. The objective of this project is to implement a digital marketing strategy through creative content formats and paid advertising to build brand recognition for Michil MSME on Instagram and TikTok platforms. The brand recognition built through this initiative is expected to improve brand visibility and expand consumer reach, particularly in the Bandung area, through effective marketing communication. This project adopts a method that combines creative content and paid advertising approaches. Data collection is based on several analyses, including empathy maps, SWOT, TOWS, and buyer personas, to gather data on consumer content pillar preferences used in designing a content calendar. The analysis and data were obtained through interviews with Michil’s customers and owner, as well as direct observation of Michil’s digital marketing activities. The research results indicate that the implementation of digital marketing through creative content and paid advertisements can increase the number of followers, likes, and account reach. These findings demonstrate that creative content formats and the use of paid ads on Instagram and TikTok platforms significantly contribute to enhancing Michil’s brand recognition. Based on this project, the author recommends that Michil become more active in developing interactive content through social media management and allocate a more strategic budget for paid advertisements to reach a broader target audience.